1991
DOI: 10.1083/jcb.112.3.479
|View full text |Cite
|
Sign up to set email alerts
|

The role of integrins in the maintenance of endothelial monolayer integrity.

Abstract: Abstract. This paper shows that, in confluent human umbilical vein endothelial cell (EC) monolayers, the integrin heterodimers c~2/3~ and ot5/3~, but not other members of the/3~ subfamily, are located at cell-cell contact borders and not at cellular free edges. Also the cry chain, but not its most common partner/33, that is widely expressed in EC cell-matrix junctions, is found at cell-cell borders. In EC monolayers, the putative ligands of oe2/3~ and o~5/3t receptors, i.e., laminin, collagen type IV, and fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
2
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(164 citation statements)
references
References 72 publications
4
157
2
1
Order By: Relevance
“…Direct evidence that underscores the physiologic significance of integrin-matrix interactions in vascular integrity comes from the studies showing that disruption of integrin-ECM interaction with RGD peptides increases venular permeability by 2-to 3-fold in vivo 43 and reduces the barrier properties of endothelial monolayers. 44 In mature EC cultures, ␣V␤3 also localizes to and maintains the integrity of the junctions 45 and decreased ␤3 expression with siRNA increases permeability. 46 Mechanistically, it has been suggested that this integrin collaborates with other intercellular molecules to form lateral junctions and specifically participates in formation of adherens junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence that underscores the physiologic significance of integrin-matrix interactions in vascular integrity comes from the studies showing that disruption of integrin-ECM interaction with RGD peptides increases venular permeability by 2-to 3-fold in vivo 43 and reduces the barrier properties of endothelial monolayers. 44 In mature EC cultures, ␣V␤3 also localizes to and maintains the integrity of the junctions 45 and decreased ␤3 expression with siRNA increases permeability. 46 Mechanistically, it has been suggested that this integrin collaborates with other intercellular molecules to form lateral junctions and specifically participates in formation of adherens junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial lining integrity is achieved by the presence of tight, adherent, and gap junctions between cells 21 and by surface integrins such as a2/31 or a5/31, whereas extracellular matrix proteins such as fibronectin or laminin do not seem to significantly interfere. 22 Because it has been demonstrated that integrins are mainly distributed at cell-cell contacts, a reduction in the surface area available for cell-cell interactions might greatly contribute to the fragility of the endothelial lining. In both adult and old animals, moreover, the subintimal space is bigger, sometimes swollen, and generally rich in glycosaminoglycans (visualized as toluidine blue-stained precipitates), 11 which might alter the permeability and the behavior of the intima components.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of IL-6 on SC cell monolayer permeability were measured using the method described by Langeler and van Hinsbergh [33], and modified by Lampugnani et al [34]. Briefly, SC primary cultures at passage 3 were grown in Transwell cell culture chambers (0.4 μm pore size, polyester filters, from Corning Life Sciences, Acton, MA) for at least 2 weeks.…”
Section: Permeability Assays In Sc Cell Monolayersmentioning
confidence: 99%